Implementasi pendidikan multikulturalisme berbasis nilai budaya lokal dalam pengajaran di jurusan pendidikan guru madrasah ibtidaiyah - Azizah, Evatul (Maliki Interdisciplinary Journal, 2025)
Indonesia is introjud as country which rich diversity and has become a social force for develop the nation. Moreoverr, the all problems existed at country Indonesia are a view of how diversity can build aggression together with lossness. main point this article are how tothe education of multiculturalism is in PGMI learning, how to applied the application of multicultural education by lecturers to PGMI students, and what are the result of implementing the multiculturalism on students.. This research use tpype qualitative (library research), by using a model critical-descriptive. In gathering many data for analysis, field research techniquesof re and strategy interview were applied as data of primary. But, data of secondary, researchers quoted scientific works in the form of books and scientific articles. Based on the data obtained, it can be concluded that multiculturalism reflects harmony between seeking social similarities and contrasts, empowering people to follow and expand their own social and social horizons. Apply mutual respect for differences, race, ethnicity, culture, language